#TITLE_ALTERNATIVE# - ARMAN PUTRA (NIM : 12206037), HERDI
One of EOR methods which is commonly used, is surfactant injection. This study included a series of reservoir simulation for surfactant injection using Field X. The reservoir simulation applied normal production scenario as the base case. The simulation starts from January 1st 2010 until December 30th 2019. Then the result of base case was compared with results from sensitivity runs regarding the three parameters mentioned above. Later, Design of Experiment method was applied to analyse the simulation results. From this Field X case, surfactant types, oil saturation, and reservoir permeability are considered highly influential parameters in surfactant injection. Among these three parameters, surfactant type is the most influential one while the injection rate and surfactant concentration is not. The influence of surfactant type is 6 times bigger than reservoir permeability factor. Injected surfactant concentration is also a parameter which must be carefully considered. Surfactant concentration exceeding the Critical Micelle Concentration (CMC) value might prevent the surfactant injection to yield optimum result.